Anatomy of sex produced by Anatomical Travelogue and Tigress Productions for Discovery Channel. - Anatomical Travelogue (Firm).; Discovery Channel (Firm). (Silver Spring, MD Discovery Communications, 2008)
Our bodies work in specific, subtle ways for one reason: to make more humans. But what is the evolutionary science behind sex and attraction? Embark on a journey to see how biological forces build up over millennia to keep the human race running. Follow one couple as they start a family together. Get a glimpse inside the human body to see what happens to both men and women when attraction occurs. How does orgasm increase the drive to procreate? Why are humans among just 3% of all mammal species that require both a male and a female for care giving? Explore the science behind interesting facts, like why humans mate front to front when all other species prefer front to back. Anatomy of Sex takes a scientific look at an age-old subject.
Title from container.
Keywords: Sex; Generative organs -- Physiology; Sex customs; Documentary television programs